BSCI-17 TOPIRAMATE DECREASES RADIATION-INDUCED CYTOTOXIC EDEMA IN HER2+ BRAIN METASTASES VIA AQUAPORIN 4 INHIBITION. (5th August 2022) - Contreras-Zárate, Maria J; Alvarez-Eraso, Karen; Littrell, Zachary; Kwak, Gina; Ormond, Ryan; Karam, Sana D; Kabos, Peter; Cittelly, Diana
Abstract: Brain metastasis (BM) occurs in 30-40 % of breast cancer patients with Her2+ tumors, and radiation is part of the standard treatment for BM. About 10% of BM patients treated with radiation develop brain edema. We have shown that combination of Ado-trastuzumab Emtansine (T-DM1)-the main targeted therapy for metastatic Her2+ Breast Cancer- and radiation increases the risk of developing radionecrosis by 13.5-fold (Stump et al., 2019). We also showed that T-DM1 enhances radiation-induced astrocytic toxicity and cytotoxic edema through upregulation of aquaporin-4 water-transporter (AQP4). Here, we determined whether blockage of AQP4 would prevent astrocytic swelling –cytotoxic edema- in vitro and in vivo models of Her2+ BM. Results: Electron microscopy of brain cortex from mice treated with 35 Gy (single dose), showed acute astrocytic end-feet swelling and a significant increase in AQP4 expression compared with non-irradiated mice. Consistent with prior findings in murine astrocytes, primary human astrocytes (huAST) also upregulated AQP4 levels 24 h post-radiation (8 Gy), and T-DM1 treatment exacerbated this effect. AQP4 upregulation was concomitant with 4.8 fold increase in the astrocytic area (indicative of cytotoxic edema). The FDA-approved anti-epileptic and migraine prevention drug, Topiramate (TPM), which works as an AQP4 inhibitor, blocked radiation-induced astrocytic swelling in huAST in vitro. Thus, we tested whether pre-treatment with TPM could prevent radiation-induced edema in a mouse model of HER2+BMs. Mice were injected intracardially JmT1BR3 brain metastatic cells and ten days later randomized based on the total head flux to (1) Radiation + vehicle, (2) Radiation + TPM (2 days prior to irradiation), (3) Non-Radiation + vehicle, and (4) Non-radiation + TPM. TPM decreased brain-water content (a marker of brain edema) in irradiated mice as compared with vehicle-treated mice, without alteration of metastatic burden 21 days post-injection. These results suggest TPM could be repurposed as a preventive agent of radiation-induced brain edema.